2007
DOI: 10.1007/s00114-007-0302-7
|View full text |Cite
|
Sign up to set email alerts
|

New fossil ants in French Cretaceous amber (Hymenoptera: Formicidae)

Abstract: Recent studies on the ant phylogeny are mainly based on the molecular analyses of extant subfamilies and do not include the extinct, only Cretaceous subfamily Sphecomyrminae. However, the latter is of major importance for ant relationships, as it is considered the most basal subfamily. Therefore, each new discovery of a Mesozoic ant is of high interest for improving our understanding of their early history and basal relationships. In this paper, a new sphecomyrmine ant, allied to the Burmese amber genus Haidom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
56
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 51 publications
(56 citation statements)
references
References 21 publications
(23 reference statements)
0
56
0
Order By: Relevance
“…also, the size of the queen metasoma is relatively large in proportion to overall body size compared with that of workers due to flight muscles, but the metasoma in H. scimitarus is quite small. lastly, it is highly unlikely that the differences in pilosity as well as the proportions of the coxae, basal funicular articles, head capsule, and mandibles that are observed here are due to caste differentiation, since both workers and a gyne of H. mammuthus are known and the castes differed only in size and in minor aspects of mandibular morphology (Perrichot et al, 2007).…”
Section: Haidomyrmex Scimitarus New Speciesmentioning
confidence: 67%
See 3 more Smart Citations
“…also, the size of the queen metasoma is relatively large in proportion to overall body size compared with that of workers due to flight muscles, but the metasoma in H. scimitarus is quite small. lastly, it is highly unlikely that the differences in pilosity as well as the proportions of the coxae, basal funicular articles, head capsule, and mandibles that are observed here are due to caste differentiation, since both workers and a gyne of H. mammuthus are known and the castes differed only in size and in minor aspects of mandibular morphology (Perrichot et al, 2007).…”
Section: Haidomyrmex Scimitarus New Speciesmentioning
confidence: 67%
“…Perrichot et al (2007) reported the earliest fossil evidence for ant sociality (i.e., castes) in H. mammathus, after discovering both a gyne and two workers in the same deposit. as with all sphecomyrmines, both Haidomyrmex and Haidomyrmodes possess this shortened scape, and so while, again, there is no direct evidence for sociality in Haidomyrmex, there would appear to be none against it at this time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Even then, the insertion of these fossils into a molecular-based phylogenetic tree has been achieved only indirectly by following the fossil's traditional taxonomic assignment rather than as a result of phylogenetic analysis combining both extinct and extant terminals. Clearly, the oldest known ant fossils, those currently classified into exclusively extinct taxa, have the potential to provide the best calibration points for deep nodes and thus increase the accuracy of divergence-time estimations for Formicidae (Perrichot et al, 2007b). Building a comprehensive morphological data set is thus the first step necessary for the incorporation of these diverse and important fossil ant faunas into the reconstruction of ant phylogeny.…”
mentioning
confidence: 99%